2008
DOI: 10.1080/01443610802421858
|View full text |Cite
|
Sign up to set email alerts
|

Postgraduate trainees' assessment of the educational value of ward rounds in obstetrics and gynaecology

Abstract: Ward rounds have been regarded as a traditional forum for the teaching and training of trainees. The aim of this research project was to look at what role ward rounds play in the medical education of trainees in obstetrics and gynaecology. A questionnaire comprising 10 statements devised around the theme of quality of medical education and the overall experience of ward rounds was distributed at the Specialist Registrars monthly training days. A total of 46 completed questionnaires were received. The ward roun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…This implies that ward rounds are underutilized as a way of teaching medical students, despite them being the most frequently undertaken bedside activity. Similar results have been noted in previous studies, where learners felt that ward round teaching sessions did not meet their expectations 10,1720. Our students also reported that the medical ward rounds are better than the surgical ones.…”
Section: Discussionsupporting
confidence: 90%
“…This implies that ward rounds are underutilized as a way of teaching medical students, despite them being the most frequently undertaken bedside activity. Similar results have been noted in previous studies, where learners felt that ward round teaching sessions did not meet their expectations 10,1720. Our students also reported that the medical ward rounds are better than the surgical ones.…”
Section: Discussionsupporting
confidence: 90%
“…These include focusing more on senior trainees leading ward rounds and being supervised by consultants. It is vital that trainees are encouraged and supported to lead ward rounds, particularly in light of the findings by Qureshi and Swamy that SpRs did not have opportunities to do so 22. Other benefits will be the use of reflection, an important part of the adult learning cycle when trainees compare self-assessment and feedback from members of the team.…”
Section: Discussionmentioning
confidence: 99%
“…Feedback on performance has been recognised as an important educational tool 1,10,11 . Furthermore consultant‐led ward rounds have been recognised as an educational opportunity in other specialities, including medicine, paediatrics and gynaecology 1,7,12–15 . Thus the results from this study should be extrapolated to other front‐line specialties, such as medicine, orthopaedics, paediatrics and gynaecology, all of which tend to have similar admission and review policies.…”
Section: Discussionmentioning
confidence: 95%